RISK ASSESSMENT IN THE ISLAMIC CLOTHING SUPPLY CHAIN MANAGEMENT USING BEST-WORST METHOD - Sumarliah, Eli (UNISSULA, 2021)
Almost a quarter of the world's population is Muslim; thus, the Islamic clothing industry is an important global business segment. Despite the immense and emerging market size of the Islamic clothing industry worldwide, there is still a scarcity of research concentrated on Islamic clothing products in the field of supply chain risk management. No previous studies comprehensively examine and provide a systematic agenda to alleviate risks in the Islamic clothing supply chain (ICSC) management. The study presents the bestâ€“worst method to examine the ICSC's risks. Through an in-depth literature review and specialists' points of view, the study identifies critical risks in the ICSC and ranks them based on their importance. The proposed findings support corporate leaders, researchers, and policymakers, focusing on the Islamic clothing business, to continually examine the risks significantly influencing their ICSCs. Firms can concentrate on the most significant supply chain risks and build effective alleviation strategies.Â